The Analogy Between the Tradition Chinese Acupuncture and Phlebotomy in Medieval Bohemia - Alexandr Ivanov (Medical Association of Pharmacopuncture Institute, 2019)
The common opinion is that in Europe acupuncture was introduced in China at the end of the XVII century. However there are some publications, which describe the similar treatment method in the Stone Age Europe. From ancient to late middle century theoretical and practical aspects of medieval medicine in Europe were very similar to the Tradition Chinese medicine. So it is possible that historical phlebotomy in Europe (bloodletting) played the same role as the acupuncture in the Chinese therapy and they had one scientific source. In this article we are comparing the modern acupuncture with some Bohemian medical tractates (Practica medicinalis by Sigismundus Albicus from 1408-1424, De sanguinis minucione by Cristannus de Prachaticz from 1430). We can see the close relationship between localizations and indications of medieval phlebotomy and modern acupuncture points. 40% of the bloodletting points have close localization with the modern acupuncture points and 57% of their indications are common or very similar. The similarity of two methods may be explained in two ways. First is a common scientific source and intensive interaction and crosscultural transmission of knowledge during medical development in China and Europe up to the beginning of the XV century. This possibility indicates also some linguistic coincidences. On the other hand, both methods could have been developed separately based on common clinical empire and objective neuro-physiological patterns of human body.